The Bibliometric Analytical Tessiture of COVID-19 International Production in the context of Social and Natural Sciences areas (Research, Society and Development, 2021)
The article aims to analyze the international scientific production of the new coronavirus (COVID-19) from the perspective of social and natural sciences, aiming to understand the characteristics of scientific publications. Bibliometric analysis was performed as a methodological procedure, using bibliometric methods such as evaluative techniques and relational techniques using the VOSviewer program. The research protocol consisted of analyzing articles referring to the themes of COVID-19 in the context of the areas of social and Natural Sciences, based on the Web of Science database covering the year 2020. Two filtering steps were performed. In the first, it was decided to keep only scientific articles in English as types of documents and, in the second, the inclusion of research areas within the scope of the theme under study, totalling, in the end, 379 articles. The next stage consisted of an evaluation related to the research areas, journals, countries, references with the highest number of citations and the most relevant studies of the H factor (H-index). The use of the VosViewer software enabled groups (cluster) based on co-quotation and the co-occurrence networks of keywords. The results demonstrate that the most influential institutions in research related to the COVID-19 pandemic are concentrated in countries such as China (22.9%) in the universe, followed by Italy, the United States, England, Canada, Australia, India, Spain, Brazil and Germany. The most relevant journals in terms of publication, of the 51 journals identified, are: International Journal of Environmental Research and Public Health and Science of the Total Environment, The reference work is Immediate Psychological Responses and Associated Factors during the Initial Stage of the 2019 Coronavirus Disease (COVID-19) Epidemic among the General Population in China. The keyword map presented coronavirus as the central theme of the map followed by terms such as outbreak, confinement, mortality, public health, China, crisis, risk, management, model, performance, behaviour, resilience, uncertainty, mental health, anxiety, infection, knowledge, depression, psychological impact and stress. In addition, an analysis of the articles considered referenced in the citations network was also performed, highlighting the main objectives and results of each study. Evidencing, therefore, the emergence and relevance of the theme and how it has been explored.